Genetic Insights into Poaceae Forages:A Review of Current Marker Studies - Bayhan, Bora; Baran, Nurettin (My University, 2023)
Forage variety development for diversified environmental conditions may benefit from the use of genomic-based breeding procedures. In today's conditions, molecular markers are used by researchers in this field to track loci and genome regions in crop breeding studies. Although earlier characterization efforts yielded useful information, morphological traits and RAPD markers have limitations when used together for genetic diversity research. Different combinations of methodologies are required for diversified aims to study different forage species at the genetic level and to connect micro level traitsto macro level traits.
Keywords: Poaceae; Genetic diversity; Forages; M arkers; M olecular characterization